2023
DOI: 10.1186/s43591-023-00065-3
|View full text |Cite
|
Sign up to set email alerts
|

Microplastics analytics: why we should not underestimate the importance of blank controls

Michael J. Noonan,
Nicole Grechi,
C. Lauren Mills
et al.

Abstract: Recent years have seen considerable scientific attention devoted towards documenting the presence of microplastics (MPs) in environmental samples. Due to omnipresence of environmental microplastics, however, disentangling environmental MPs from sample contamination is a challenge. Hence, the environmental (collection site and laboratory) microplastics contamination of samples during processing is a reality that we must address, in order to generate reproducible and reliable data. Here we investigated published… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In this study, samples were prepared in a fume hood because of the digestion process and hypothesizing that this would have diminished procedural blank MP levels. However, Noonan et al [37] recently reported that blank controls from fume-hood-prepared samples were higher compared to those prepared on the laboratory bench or using a laminar flow hood. Munno et al [38] recommended blank subtracting through a combination of particle characteristics, such as color, morphology, and size fraction, stating that this approach likely results in final MP characteristics that are most representative of the sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, samples were prepared in a fume hood because of the digestion process and hypothesizing that this would have diminished procedural blank MP levels. However, Noonan et al [37] recently reported that blank controls from fume-hood-prepared samples were higher compared to those prepared on the laboratory bench or using a laminar flow hood. Munno et al [38] recommended blank subtracting through a combination of particle characteristics, such as color, morphology, and size fraction, stating that this approach likely results in final MP characteristics that are most representative of the sample.…”
Section: Resultsmentioning
confidence: 99%
“…The use of blank controls is critical in evaluating the extent and magnitude of this contamination. However, a study on 59 MP published articles from 2021 to 2022 found that one in five research studies failed to use blank controls [37] When blank controls were used and reported, a wide range of methods were used from simply reporting blank levels to use of statistical methods and blank correction of samples based on size, color, and MP type [38]. For example, Noonan et al [38] reported that almost 60% of studies that used blank controls did not correct sample concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly relevant in situations when it is necessary to correct for underestimation of microplastics due to low but reproducible recovery rates (Hermsen et al, 2018;Koelmans et al, 2019). In addition to the positive controls, which are designed to minimize influence of internal loss during sample pretreatment, further precautions should be taken to eliminate contamination from external sources (Noonan et al, 2023). Contamination can consist of airborne synthetic components so it is crucial to keep the samples sealed or covered whenever possible both in the field (over the course of sampling and transport) and in the laboratory (during the analysis) (Vandermeersch et al, 2015;Wesch et al, 2016).…”
Section: Data Quality Assessment Of the Reviewed Studiesmentioning
confidence: 99%
“…Different pre-treatments of samples have been developed to digest samples (mostly based on KOH and H 2 O 2 ) and thus to allow analysis of microparticles [ 22 ]. Procedural blanks used as negative controls to monitor the eventual contamination of samples by MPs to avoid equivocal results and biased conclusions took on a great importance too [ 23 ]. Nevertheless, the aforementioned procedures are not usually strictly adopted altogether, thus results must be taken with caution.…”
Section: Evidence Of Microplastics In Humanmentioning
confidence: 99%